Screening for Suicidal Ideation and Attempts among Emergency Department Medical Patients: Instrument and Results from the Psychiatric Emergency Research Collaboration. Issue 3 (16th February 2013) - Allen, Michael H.; Abar, Beau W.; McCormick, Mark; Barnes, Donna H.; Haukoos, Jason; Garmel, Gus M.; Boudreaux, Edwin D.
<x xml:space="preserve">Abstract</x> Joint Commission National Patient Safety Goal 15 calls for organizations "to identify patients at risk for suicide." Overt suicidal behavior accounts for 0.6% of emergency department (ED) visits, but incidental suicidal ideation is found in 3%–11.6%. This is the first multicenter study of suicide screening in EDs. Of 2, 243 patients in six diverse emergency settings, 1, 068 (47.7%) were screened with a brief instrument. Depression was endorsed by 369 (34.5%); passive suicidal ideation by 79 (7.3%); and active suicidal ideation by 24 (2.3%). One hundred thirty‐seven (12.8%) reported prior attempts, including 35 (3.3%) with current suicidal ideation. Almost half of those with current ideation had a prior attempt (43.8%) versus those without current ideation, 10.3%, χ2 (1) = 75.59, p < .001. Twenty cases (25%) were admitted to medical services, but only 10 (12.5%) received mental health assessment; none were admitted directly to a psychiatry service. The prevalence of suicidal ideation here is similar to previous studies but the frequency of prior attempts has not been reported. The 35 cases with current ideation and prior attempt are at risk. As they did not present psychiatrically, they would likely have gone undetected. Despite reporting these cases to clinical staff, few received risk assessment.